Analysing the State’s Laws on Religious Education in Post-New Order Indonesia - Mohamad Yusuf; Carl Sterkens (Al-Jami'ah: Journal of Islamic Studies, 2015)
This article aims to analyse the Indonesian State’s laws regarding models of religious education, by evaluating Law No. 20/2003, concerning the national system of education and other related laws. Two questions are highlighted: What type of religious education is favoured by Indonesian state? Does the preference for a certain type of religious education reflect a specific vision of the state-religion relationship? Our data consisted of two sources: the State’s law on national education system, Law No. 20/2003, and the minutes of the Indonesian parliament meeting approving the law. We found that Law No. 20/2003 expresses the preference of the government for a mono-religious model. Indonesia is categorized as having preferred treatment for some religions or support for a particular religious tradition. This categorisation is confirmed by the results of our research findings indicated by the preferential treatment delivered by the State, and the State’s legislation and regulations on religion.[Tulisan ini menganalisis legislasi negara terhadap pendidikan agama dengan cara mengevaluasi UU No. 20/2003 tentang Sistem Pendidikan Nasional beserta perundang-undangan terkait lainnya. Dua pertanyaan berusaha untuk dijawab dalam tulisan ini, yaitu: Model pendidikan agama yang bagaimana yang menjadi preferensi negara? Apakah preferensi tersebut merefleksikan visi negara terhadap model relasi negara-agama tertentu? Tulisan ini merujuk kepada dua data utama, yaitu: UU No. 20/2003 tentang Sistem Pendidikan Nasional serta Risalah Rapat Paripurna ke-35 DPR RI tahun 2003 yang mengesahkan UU No. 20/2003. Penelitian ini menemukan bahwa UU Sistem Pendidikan Nasional merefleksikan preferensi negara terhadap model pendidikan agama mono-relijius. Model pendidikan mono-religius ini merefleksikan preferensi negara terhadap model relasi negara-agama preferensial; negara mengakui lebih dari satu agama resmi dan memberi dukungan kepada institusi-institusinya, yang direfleksikan melalui legislasi dan peraturan terkait agama.]